IMPLEMENTATION OF ONLINE IMPULSIVE PURCHASING WITH DIGITAL PAYMENT METHODS AS A MODERATOR IN NORTH SULAWESI - Najwa Bachdar; Meykel Djuuna; Fricy Rumintjap (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of digital promotion and local culture on digital impulsive buying, with digital payment methods as a moderating variable. This study uses the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with primary data collected from e-commerce users in North Sulawesi, Indonesia. The results show that digital promotion has the most significant influence on impulsive purchasing behavior, followed by local culture, which also contributes positively. However, digital payment methods do not significantly moderate the relationship between the variables studied. These findings highlight that personalized digital promotion strategies and the integration of local cultural values effectively increase consumers' emotional engagement in online purchases. This study provides practical implications for e-commerce players, digital MSMEs, and fintech developers to strengthen digital promotion strategies and financial literacy throughout Eastern Indonesia. Keywords: Digital promotion, local culture, digital payment methods, impulsive buying, e-commerce